An act of performance: Exploring residents' decision‐making processes to seek help. Issue 6 (18th February 2021) - Jansen, Iris; Stalmeijer, Renée E.; Silkens, Milou E. W. M.; Lombarts, Kiki M. J. M. H.
Abstract: Context: Residents are expected to ask for help when feeling insufficiently confident or competent to act in patients' best interests. While previous studies focused on the perspective of supervisor‐resident relationships in residents' help‐seeking decisions, attention for how the workplace environment and, more specifically, other health care team members influence these decisions is limited. Using a sociocultural lens, this study aimed to explore how residents' decision‐making processes to seek help are shaped by their workplace environment. Methods: Through a constructivist grounded theory methodology, we purposively and theoretically sampled 18 residents: 9 juniors (postgraduate year 1/2) and 9 seniors (postgraduate year 5/6) at Amsterdam University Medical Centers. Using semi‐structured interviews, participating residents' decision‐making processes to seek help during patient care delivery were explored. Data collection and analysis were iterative; themes were identified using constant comparative analysis. Results: Residents described their help‐seeking decision‐making processes as an 'act of performance': they considered how asking for help could potentially impact their assessments. They described this act of performance as the product of an internal 'balancing act' with at its core the non‐negotiable priority for providing safe and high‐quality patient care. With this in mind, residents weighed up demonstrating the ability to work independently, maintaining credibility and becoming an accepted member of the health care team when deciding to seek help. This 'balancing act' was influenced by sociocultural characteristics of the learning environment, residents' relationships with supervisors and the perceived approachability of other health care team members. Conclusions: This study suggests that sociocultural forces influence residents to experience help‐seeking as an act of performance. Especially, a safe learning environment resulting from constructive relationships with supervisors and the approachability of other health care team members lowered the barriers to seek help. Supervisors could address these barriers by having regular conversations with residents about when to seek help. Abstract : Noting that interviewed residents described asking for help as an act of performance, Jansen et al. use a sociocultural lens to address the role of the healthcare team and learning environment in help‐seeking.